2017
DOI: 10.1111/1750-3841.13926
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Short‐Time Temperature Abuse on the Microbial and Sensory Quality of Chilled Saithe (Pollachius virens) Fillets

Abstract: The observations show the importance of maintaining a low temperature in fish, even for a short period such as during processing. Any delays, such as due to buffering or mechanical failure, may accelerate spoilage of chilled products during subsequent storage. This effect is even more pronounced when products are packed in bulk volumes as the cooling rate is much slower than the piece-by-piece cooling rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…QIM methodologies are being widely applied to various fish species [36,37,38,39] and products [40,41], reflecting the importance of the methodology for fish freshness evaluation and shelf-life prediction. Besides the expected differences between different species, it is also possible to obtain variations in the values of the evaluation parameters for the same fish species, mainly due to storage conditions or type of product [42,43,44,45], reflecting the expected variance that other methods do not incorporate (i.e., EU scheme).…”
Section: Discussionmentioning
confidence: 99%
“…QIM methodologies are being widely applied to various fish species [36,37,38,39] and products [40,41], reflecting the importance of the methodology for fish freshness evaluation and shelf-life prediction. Besides the expected differences between different species, it is also possible to obtain variations in the values of the evaluation parameters for the same fish species, mainly due to storage conditions or type of product [42,43,44,45], reflecting the expected variance that other methods do not incorporate (i.e., EU scheme).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, temperature fluctuation is inevitable for frozen large yellow croaker during cold storage, transportation and sales. Many researchers found that the temperature fluctuation during the storage had an irreversible impact on the quality of fish ( Göransson et al, 2018 , Mu et al, 2017 ). Margeirsson et al (2012) also believed that in the simulation of cold chain logistics, temperature fluctuations were the main reason for the shortened shelf life of cod.…”
Section: Introductionmentioning
confidence: 99%